Higgs Mass Constraint on a Low Scale SUSY Model - Hieu, Tran Minh; Huong, Nguyen Thu; Trang, Trieu Quynh (Communications in Physics, 2017)
Randal-Sundrum models have an interesting feature that an effective physical scale can be generated from a much larger one of the underlying theory. In this paper, we investigate a model of supersymmetry in the Randall-Sundrum spacetime with a low cutoff scale. Due to the warp factor, the Kaluza-Klein scale is warped down to \(O\)(100) TeV. With the MSSM superfields living in the bulk, the soft SUSY breaking terms of the 4D effective theory are derived from the original 5D Lagrangian by integrating out the extra-dimension. We examine the constraint of the Higgs boson mass measurement on the model. As a result, the viable parameter space with the ability to reproduce a 125 GeV Higgs mass is identified. The constraint rules out parameter regions with the stop masses larger than 20 TeV. Therefore, the parameter space of the model can be explored in a future 100 TeV collider.